2014
DOI: 10.1111/eth.12246
|View full text |Cite
|
Sign up to set email alerts
|

Turning Shy on a Winter's Day: Effects of Season on Personality and Stress Response in Microtus arvalis

Abstract: Animal personalities are by definition stable over time, but to what extent they may change during development and in adulthood to adjust to environmental change is unclear. Animals of temperate environments have evolved physiological and behavioural adaptations to cope with the cyclic seasonal changes. This may also result in changes in personality: suites of behavioural and physiological traits that vary consistently among individuals. Winter, typically the adverse season challenging survival, may require in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 73 publications
(140 reference statements)
0
20
0
Order By: Relevance
“…Conversely, we found that the more active individuals within a flock were the more difficult to catch in Short Days but not in Long Days. The correlation between within‐flock activity and escape ability may rather result from short‐term adjustments to a given photoperiod (Gracceva et al., ). Furthermore, we found that several relationships between personality traits not only varied with photoperiod but also with sex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, we found that the more active individuals within a flock were the more difficult to catch in Short Days but not in Long Days. The correlation between within‐flock activity and escape ability may rather result from short‐term adjustments to a given photoperiod (Gracceva et al., ). Furthermore, we found that several relationships between personality traits not only varied with photoperiod but also with sex.…”
Section: Discussionmentioning
confidence: 99%
“…These observations thus showed that animal personality is not incompatible with behavioural plasticity as consistent interindividual differences can be maintained despite individuals’ mean reaction to an environmental change. Other studies showed that correlations between behaviours (i.e., behavioural profiles) differed between populations in sticklebacks ( Gasterosteus aculeatus ; Bell & Stamps, ), between years in flycatchers ( Ficedula albicollis ; Garamszegi et al., ) or between seasons in common voles ( Microtus arvalis ; Gracceva et al., ). Environmental conditions might thus favour different correlations between personality traits (Bell & Stamps, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an area of research that has progressed remarkably (see Bedoya-Perez et al 2013 for review) since the seminal paper on giving up densities by Joel Brown (1988). The other areas of behaviour that were covered were the fascinating study of individual behavioural 'personalities' of rodents (Gracceva et al 2014) and how knowledge of the social interactions that influence the use of the landscape by different species could provide a mechanism for using native rodent species to manage a population of the invasive black rat, Rattus rattus, in an urban-bushland interface (Banks and Smith 2015). Two other papers in this issue examine behaviour of rodents.…”
mentioning
confidence: 99%